Delphinidin-rich extracts of Hibiscus sabdariffa L. trigger mitochondria-derived autophagy and necrosis through reactive oxygen species in human breast cancer cells. (August 2016) - Wu, Cheng-Hsun; Huang, Chi-Chou; Hung, Chia-Hung; Yao, Fang-Yi; Wang, Chau-Jong; Chang, Yun-Ching
Highlights: Hibiscus anthocyanins induce autophagy and necrosis in human MCF-7 cells. Hibiscus anthocyanins trigger autophagy via the AMP-activated kinase pathway. Hibiscus anthocyanins stimulate reactive oxygen species generation. Abstract: Anthocyanins from Hibiscus sabdariffa L. (HAs) possess anticancer potential and diverse biological effects, but its correlation with human breast cancer cells and different modes of cell death is unclear. Here, we show that HAs can induce both autophagy and necrosis cell death distinct from apoptosis in MCF-7 cells. HAs could effectively reduce the viability of MCF-7 cells. Unexpectedly, HAs failed to stimulate the apoptosis-related proteins Bcl2 and Bax. Autophagy was characterized by acridine orange staining, LC3 (light chain 3) activation and AMPK (AMP-activated kinase) phosphorylation. The necrosis death was confirmed by annexin V/propidium iodide (PI) double-positive detection and PI uptake assay. HAs-elicited responses were accompanied by reactive oxygen species (ROS) elevation and mitochondrial membrane potential collapse. Moreover, N-acetylcysteine (NAC) reversed HAs induced cell viability. Our study is the first to report that HAs-modified mitochondrial function triggers cell death by autophagy and necrosis in MCF-7 cells rather than programmed cell death.